Diversifying away from Russian Gas: The Сase of Poland - Csaba Weiner (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
Commercial and geopolitical realities drive Central and East European (CEE) countries to reduce dependence on Russian gas imports and enhance security of supply. While, in general, these countries are heavily dependent on Russian gas, they have different conditions, varying approaches towards dependence and security of supply, and thus give differing energy policy answers. Diversification is a means of reducing dependence and enhancing security of supply. There are many types of diversification. To understand this complexity and assess CEE countries, we have developed a scheme of different CEE diversification options for Russian gas imports. In this article, we analyse these options and achievements for one specific country, Poland, which seeks a level of diversification that would enable ending Russian gas imports. We find that since the January 2009 Russian–Ukrainian gas crisis, Poland has taken concrete action, and it has finally made huge progress in gas import source diversification. New pipeline and liquefied natural gas capacities could allow Poland to reach its goal, though the existing import portfolio still lacks a supply contract for Norwegian gas imports to be supplied through the yet-to-be-built Danish–Polish Baltic Pipe. Without these amounts, Russian supplies could be necessary, or at least Russian molecule supplies. In contrast, domestic gas production does not seem to provide a grounding for diversification. Albeit energy efficiency and conservation are significant opportunities, reducing total gas consumption is also not possible, mainly due to the movement away from coal. From this point of view, sectoral diversification has limited real relevance, as it can only limit further gas demand growth. With the termination of large-quantity long-term Russian gas supplies, transit diversification will also bear less importance. Nevertheless, it remains to be seen whether the termination of Russian (long-term) gas supplies will actually serve security of supply, as diversification alone does not inevitably lead to achieving this goal.